Temperamental Shyness, Frontal EEG Theta/Beta Ratio, and Social Anxiety in Children. Issue 5 (22nd April 2021) - Poole, Kristie L.; Hassan, Raha; Schmidt, Louis A.
Abstract : The authors examined how children's frontal electroencephalogram (EEG) theta/beta ratio—an index of neurocognitive control—changed from baseline to a social stressor, and whether these EEG changes moderated the relation between temperament and anxiety. Children ( N = 152; M age = 7.82 years, 52% male, 81% White) had their EEG recorded during a baseline and speech anticipation condition. Children's frontal theta/beta ratio decreased from baseline to speech anticipation, and this baseline‐to‐task change moderated the relation between temperamental shyness and social anxiety. Temperamental shyness was related to higher state and trait social anxiety only among children with large baseline‐to‐task decreases in theta/beta ratio. Findings are consistent with theoretical models hypothesizing that temperamentally shy children with heightened neurocognitive control may be at greater risk for anxiety.